2006
DOI: 10.1007/bf03194596
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters and correlations of collar rot resistance with important biochemical and yield traits in opium poppy (Papaver somniferum L.)

Abstract: Collar rot, caused by Rhizoctonia solani Kühn, is one of the most severe fungal diseases of opium poppy. In this study, heritability, genetic advance and correlation for 10 agronomic, 1 physiological, 3 biochemical and 1 chemical traits with disease severity index (DSI) for collar rot were assessed in 35 accessions of opium poppy. Most of the economically important characters, like seed and capsule straw yield per plant, oil and protein content of seeds, peroxidase activity in leaves, morphine content of capsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
1
5
1
Order By: Relevance
“…In such cases a simple selection model would be advantageous to obtain the desired gain because no additional gain can be achieved by using other sophisticated models (Singh et al 2003b). Similar to our results, Trivedi et al (2006) have also observed high heritability along with high values of genetic advance for seed and straw yield and DSI for collar rot. High heritability coupled with high GA and Genotypic coefficient of variation (GCV) for the traits like papaverine, thebaine and narcotine have also been reported in opium poppy (Yadav et al 2006).…”
Section: Genetic Variability and Selection Parameters For Dm Resistansupporting
confidence: 92%
See 3 more Smart Citations
“…In such cases a simple selection model would be advantageous to obtain the desired gain because no additional gain can be achieved by using other sophisticated models (Singh et al 2003b). Similar to our results, Trivedi et al (2006) have also observed high heritability along with high values of genetic advance for seed and straw yield and DSI for collar rot. High heritability coupled with high GA and Genotypic coefficient of variation (GCV) for the traits like papaverine, thebaine and narcotine have also been reported in opium poppy (Yadav et al 2006).…”
Section: Genetic Variability and Selection Parameters For Dm Resistansupporting
confidence: 92%
“…The heritability estimates were high for most of the traits and ranged from 39% for diameter of the central capsule to 99.81% for seed yield/central capsule (Table 4). There have been similar reports of high heritability for characters like plant height, days to 50% flowering, days to maturity, leaf area per plant, straw and seed yield per plant, oil and protein content of seeds, morphine content of straw, DSI for collar rot (Trivedi et al 2006;Jain et al 2005;Pant et al 1999), morphine, codeine, thebaine and narcotine contents (Yadav et al 2006;Briza 1983). There have also been reports of low heritability of some characters like number of capsules per plant (Trivedi et al 2006;Briza 1983).…”
Section: Genetic Variability and Selection Parameters For Dm Resistanmentioning
confidence: 77%
See 2 more Smart Citations
“…These results indicate that the landraces in this study are not good material for improvement of stigma number. Bhandari (1990) suggested that landraces with more stigmas should be selected for morphine content improvement in opium poppy breeding and it was later shown that stigma number is strongly correlated with morphine content (Trivedi et al 2006). However, no correlation was seen in the current work.…”
Section: Morphological Trait Diversitycontrasting
confidence: 52%